2020
DOI: 10.1152/ajplung.00234.2019
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of macrophage migration inhibitory factor in pulmonary hypertension

Abstract: Pulmonary hypertension (PH) is a life-threatening condition arising from the loss and obstructive remodeling of the pulmonary arteries, leading to the sustained elevation of pulmonary arterial pressure (PAP) and pulmonary vascular resistance (PVR) and subsequently right ventricular (RV) failure and death. PH encompasses a group of multifactorial diseases, such as pulmonary arterial hypertension (PAH) and chronic thromboembolic PH, for which there is no treatment that can stop or reverse the progression of remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…As a pleiotropic upstream proinflammatory mediator, MIF is a promising molecular target for PH therapy because MIF contributes to perivascular inflammation and pulmonary artery remodeling (Jalce & Guignabert, 2020). In addition, the increase in MIF levels in the pulmonary artery of PH will induce the proliferation of pulmonary vascular smooth muscle cells, leading to pulmonary artery remodeling (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As a pleiotropic upstream proinflammatory mediator, MIF is a promising molecular target for PH therapy because MIF contributes to perivascular inflammation and pulmonary artery remodeling (Jalce & Guignabert, 2020). In addition, the increase in MIF levels in the pulmonary artery of PH will induce the proliferation of pulmonary vascular smooth muscle cells, leading to pulmonary artery remodeling (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The concept that perivascular inflammation may be a driver and marker of vascular remodeling has also been explored recently as another approach for molecular imaging of disease activity in PAH, based on a body of literature that has identified a variety of perivascular inflammatory lineages in human PAH and experimental PH lung tissues. [167][168][169][170] A 68 Ga-substituted conjugate molecule containing mannosylated human serum albumin protein ( 68 Ga-NOTA-MSA) has been used as a PET-CT imaging probe targeting macrophages expressing the mannose receptor (CD206). 171 In support of enhanced macrophage activity associated with PH biology, the investigators found transcriptional signatures consistent with increased macrophage activation, and immunohistologic evidence of CD206 + macrophage infiltration in the perivascular tissues of rats with monocrotaline-induced PH, all of which were progressive with development of the PH phenotype.…”
Section: Ga-nota-msa Pet-ctmentioning
confidence: 99%
“…We further examined specific ligand-receptor interactions and found that signaling molecules known to play a role in PAH such as vascular endothelial growth factor A (VEGFA) (32), C-X-C motif chemokine ligand 12 (CXCL12) (33,34), and macrophage migration inhibitory factor (MIF) (35,36) were not only differentially active in PAH models compared to control but also specific to cell-cell communication involving EA2 but not EA1 (Figure 2C) nor EC (Figure E3).…”
Section: Ea2-specific Cell-to-cell Signaling Network Are Activated In Pahmentioning
confidence: 99%